Silicone ventilation catheter for high-frequency jet ventilation in interventional pulmonology; a new approach - Onur Küçük; Ayperi Öztürk; Aydın Yılmaz; Ali Alagöz (BMC Pulmonary Medicine)
Abstract Background/aim This study evaluated the efficacy of high-frequency jet ventilation (HFJV) using a silicone catheter in patients undergoing rigid bronchoscopy (RB). Materials and methods Following necessary approval for a retrospective clinical and experimental study, the data of patients who underwent HFJV using a silicone catheter during RB under general anesthesia through interventional pulmonology (IP) between January 2024 and August 2024 were analyzed. Prior to the study, flow/thermography tests were conducted to assess the efficacy of the silicone catheter. Arterial blood gas (ABG) analysis before, during, and after anesthesia as well as patient hemodynamic and oxygen saturation (SpO2) data recorded during the procedure were evaluated. Patients were observed for up to 24 h following the procedure. The procedure included the following steps: (1) HFJV application with Evone® (Ventinova, Eindhoven, Netherlands) ventilator after intubation with an orotracheal silicone catheter; (2) HFJV termination and manual ventilation (MV) application in cases of hypoxia, hypercapnia, and hemodynamic instability; (3) flow-controlled ventilation (FCV) with a laryngeal mask or tracheal intubation in patients who cannot be managed with MV; and (4) close hemodynamic monitoring as well as ABG analysis during the procedure. Result A total of 25 patients were included in the study. The median duration of the procedure was 35 min. In 21 (84%) patients, the procedure was successfully performed with HFJV using a silicone ventilation catheter. In these successful cases, the hemodynamic parameters and ABG values remained within normal limits throughout the procedure. The median values of arterial oxygen partial pressure (PaO2), arterial carbon dioxide partial pressure (PaCO2), SpO2, and pH were 210 mmHg, 41.6 mmHg, 99.4%, and 7.37, respectively, when considering the worst ABG values during the procedure. Hypoxia (SpO2 < 90%) was detected in 4% (n = 1) of patients, while hypercarbia (PaCO2 ≥ 50 mmHg) was observed in 16% (n = 4). The utilization of a Y-stent was necessary in one patient (4%). One patient (4%) experienced severe bleeding during the resection process, and one (4%) patient underwent orotracheal intubation. Postoperative pulmonary complications or adverse events were not observed in any patient. Conclusion The findings of the present study demonstrated that the utilization of silicone catheters in conjunction with HFJV is both safe and efficacious for IP and RB procedures. These results suggest that HFJV with a silicone catheter may be a viable option in RB procedures. Clinical trial number It cannot be applicable because it is a retrospective study.